Degree programme for executives - The Star (2012)
IN support of the nation's objectives and in line with the development of a Global Ekonomy and the country's rapid pace of developmrnt,the Executive programme unit (UPE) by University Putra Malaysia's Faculty of Economics and Management (PEP) was created to realise the concept of lifelong learning.The prepared programmes are opportunities for working candidates to enhance their level of education and knowledge whilst excelling in their chosen career.